Analisis Manajemen Resiko Pada UMKM Oprit Fried Chiken - Cindi Septian, Yosef; Cindi Firmansyah, Wisnu; Agustina, Bilqis Putri (Universitas Serambi Mekkah, 2024)
The aim of this research is to identify the risk management process, conduct research on risks that may arise and analyze the strategies that will be carried out by MSMEs in handling or managing these risks in the city of Bandung. This research was carried out in accordance with the risk management process (ISO: 31000), namely risk identification, risk analysis, risk evaluation and risk treatment. The risks obtained are the risks that occur most often and are in the high level category in